The Characteristics of Korean Artists in Pronouncing English Words on Korean Reality Shows: A Generative Phonology Perspective - Pratidina, Regina Galuh Prameswari; Agus Subiyanto (Universitas Negeri Semarang, 2024)
South Korea's cultural industry, known as the